An Analysis of Translation Strategies Used by Students in Translating Idioms at the Second Grade of SMA Kalam Kudus - Sinambela, Erika; Manik, Sondang; Siregar, Roswani; Manurung, Lastri Wahyuni; Saragi, Christina Natalina (International Journal of Membrane Science and Technology, 2023)
The research is aimed at describing the strategies used by translator. The strategies here is that the translator deals with idioms. The study is qualitative analysis. The data of this study were analyzed by using two steps. First, analyzing the translation work and the reason why the translators did it. Second, writing them down and comparing the source text and the target text. The strategies used in the subtitle translation according to Baker’s theory consists of four strategies of translation, those are: translation by using an idiom of similar meaning and form, translation by using an idiom of similar meaning but dissimilar form, translation by paraphrasing and translation by omission. There are 70 idiomatic expressions, which are divided into four part as the strategies used by the translator and, the dominant strategy used by Qoryati as the translator is translation by paraphrase which appears in 62 cases.3 of them were translated by omission. Meanwhile, 3 of them were translated by the strategy of translation using idiom of similar meaning but dissimilar form, and the last, 2 of them were translated by the strategy of translation using idiom of similar meaning and form. These strategies will help the translator to deal with the problems in translating idiomatics expressions in subtitle translation, these strategies are used in to make the result of translation not only enjoyable but also meaningful for the readers.